A Value Chain Approach to Support Southeast Asian Economic Regionalism - Craig Jones (JAS (Journal of ASEAN Studies), 2019)
This article includes an exploration of the economic data sets of the Association of Southeast Asian Nations (ASEAN) Statistics, the World Bank, and the International Monetary Fund, as well as primary regional economic initiatives and agreements to assess the strategic indicators of economic regionalism using thematic analysis. The aim of this research is to determine how Southeast Asian regionalism can circumvent vulnerabilities to another economic crisis in North America and the European Union. To correct such financial vulnerabilities, ASEAN has significantly remolded the region into a single market consisting of a 10-nation integrated production base. The ASEAN Economic Community’s main pillars are the establishment of a regional economic foundation based on comprehensive investment initiatives; the liberalization of capital markets, tariffs, and professional labor; infrastructure connectivity; regional policy integration; and free trade agreements to create a regional value chain as part of a single market and production base. The more attainable this comprehensive value-capture-and-integration process becomes, the more attractive it will appear to the global economic investment community and for business opportunities to establish a robust regional foundation. Although the process appears straightforward, capturing value is not a single phenomenon or method, but rather a multifaceted phenomenon, as explored in this study. The regional integration model seeks profitability within effective cross-border production networks and regional liberalization.